Technological Unemployment - Magdalena Klimczuk-Kochańska; Andrzej Klimczuk (The SAGE Encyclopedia of World Poverty, 2015)
Technological unemployment is a situation when people are without work and seeking work because of innovative production processes and labor-saving organizational solutions.
Keywords: O33; E24; 330; Economic Growth and Technology; Unemployment; Employment Theory; Technology and Public Policy